Impact of Life Cycle on Corporate Restructuring while in Financial Distress - Dariush Damoori (Ph.D) (Shahid Bahonar University of Kerman, 2019)
Objective: The aim of this study is to investigate the impact of life cycle on corporate restructuring while in financial distress. Method: This study uses cluster analysis to classify data, and the Dickinson cash flow patterns (2011) to calculate life cycle as well as the Zmijewski modified pattern (2005) to determine financial distress. A sample of 100 companies listed in the Tehran Stock Exchange during 2010 to 2014 was surveyed. Result: The results indicated life cycle has positive and significant effect on corporate restructuring. Also, life cycle and corporate restructuring have positive and significant effects on the level of financial distress. Additionally, results showed that corporate life cycle has positive and significant effects on financial restructuring, operational restructuring and asset restructuring, whiles life cycle lacks significant effects on managerial restructuring Conclusion: The companies use restructuring during their life cycle, and distressed companies use more restructuring strategies in the last stages of their life cycle. Hence, as companies reach the final stages of their life cycle are more likely to use these strategies. We cannot comment on presence or absence of managerial changes during different stages of the life cycle.